GENDER AND POWER DISCOURSE: HEROINE REPRESENTATION IN MARVEL FILMS THROUGH RUTH WODAK'S APPROACH - RR Roosita Cindrakasih; Rizki Hidayat; Amalliah; Flora Meliana Siahaan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the representation of female superheroes (heroines) in Marvel Studios films using Ruth Wodak's Critical Discourse Analysis approach. By examining three films: Captain America: The First Avenger, Black Panther: Wakanda Forever, and The Marvels, this study explores how the construction of gender and female power is presented in the narrative, dialogue, and visualization of female characters. Using Wodak's model, which focuses on historical, social, and political contexts, this study reveals how female representations are influenced by specific ideologies and social changes in the entertainment industry. The analysis reveals that despite the strengthening of women's roles as central and powerful characters, dominant narratives persist that subtly reproduce gender stereotypes and inequalities. This study demonstrates the importance of critically interpreting the representation of women in popular media, as well as how the construction of women's power and identity in fictional spaces also reflects gender dynamics in real society.